(untitled) (Research, Society and Development, 2022)
The present study shows the physical and chemical parameters collected in an urban river in the Eastern Amazon, they present the characteristics of the waters in the Neblina stream, which has its basin inserted in an urban center, in the city of Araguaína - TO. Therefore, the present study aims to investigate the water quality parameters of that stream, and thus allow deductions about the causes and effects of these changes. In this stream, sampling points were listed that contemplate environments from the springs to its mouth. Being, the quality of its waters, evaluated in two stages that envision two seasons (dry and rainy), respectively, August 2020 and March 2021. Adding a total of six sampling points, systematically visited in both seasons described, making up 12 samples, for all parameters analyzed here. In this way, the samples were explored in order to find values for the parameters: In Situ (Turbidity by turbidimeter; Dissolved oxygen; Electrical conductivity; Water temperature; Air temperature; pH); and Ex Situ (BOD; COD; Nitrogen series; Phosphate series; Fecal coliforms; Chlorophyll-α; Heavy metals). The parameters showed similar variations between the sampling points, with a notable data discrepancy between the mouth and head of the Neblina stream. These results show that there are higher concentrations for these parameters, directly related to the length of the route in the urban environment. Indicating a possible impact on the existing fauna and flora, which may conjecture a plausible toxicity and risks to organisms, as an admissible threat to biodiversity.